Evaluate the relation between microalbuminuria and with other biochemical parameters related to complications of type 2 diabetes - Vaidya, S. A.; Gupta, B. B.; Bhandari, Mahak; Behl, Simran; Kosta, Susmit (International Journal of Advances in Medicine, 2019)
Background: Type 2 Diabetes (T2D) with microalbuminuria have increased risk of progression to overt proteinuria, and after some time, renal failure. It is the leading cause of end-stage renal disease as a sequalae of Diabetic Nephropathy (DN) and an independent risk factor for Cardio-Vascular Diseases (CVD). Initial finding for microalbuminuria can prevent long-term complications. The objective of the present investigation was to study the relation between microalbuminuria and with other biochemical parameters related to complications of T2D. Methods: This observational study was conducted among 150 T2D patients attending to the OPD, Department of General Medicine during the time period March 2018 to April 2019. The patients were interviewed for socio-demographic details, history and clinical examination and subjected to blood investigations and Electrocardiogram (ECG). Results: Microalbuminuria was present in 47(31.3%) of the diabetics. The age group 48-63 years 18(38.3%), male gender 33(70.2%) duration of diabetes >5 years 11(23.4%). The smokers, Diabetic Retinopathy, Peripheral Neuropathy, Ischemic Heart Disease, SBP 160-170 mmHg, DBP 95-100 mmHg and 100-105 mmHg, BMI 30-35 Kg/m2, TG >250 mg/dl, LDL >110 mg/ dl and HbA1c 7.5-9 % showed a greater odds ratio and significant association (p<0.001) with microalbuminuria. Conclusions: There was an increased prevalence of microalbuminuria among patients with T2D. It also showed a significant association of major microvascular and macrovascular complications of T2D and microalbuminuria.